2017
DOI: 10.1016/j.tifs.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of toxicity equivalency factors for marine biotoxins associated with Bivalve Molluscs

Abstract: Background Seafood toxins pose an important risk to human health, and maximum levels were imposed by regulatory authorities throughout the world. Several toxin groups are known, each one with many analogues of the major toxin. Regulatory limits are set to ensure that commercially available seafood is not contaminated with unsafe levels. Scope and Approach The mouse bioassay was used to measure the toxicity in seafood extracts to determine if a sample exceeded regulatory limits. The advantage of this approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 111 publications
1
50
0
2
Order By: Relevance
“…This fact should alert health authorities to the need for potential preventive measures. The oral LD 50 (232 µg/kg BW) and NOAEL (75 µg/kg BW) values determined in this study may be used as a starting point for further risk assessment processes leading to a safe seafood level for TTX in the EU [22]. …”
Section: Discussionmentioning
confidence: 99%
“…This fact should alert health authorities to the need for potential preventive measures. The oral LD 50 (232 µg/kg BW) and NOAEL (75 µg/kg BW) values determined in this study may be used as a starting point for further risk assessment processes leading to a safe seafood level for TTX in the EU [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that OA is less toxic than DTX1 with oral LD 50 values of 760 and 487 µg kg -1 bw respectively, while DTX2 is the less potent with an oral LD 50 of 2262 µg kg -1 bw [29]. Those LD 50 values were lower than previously reported and differences could be related to the quality of the marine toxins utilized [19,[24][25][26][27][28]. Based in these results the order of oral toxic potency is DTX1 > OA > DTX2 in agreement with the PP2A inhibitory potency.…”
Section: Discussionmentioning
confidence: 65%
“…The previously described lethal oral doses of OA were 400 [21] 600 [22] and between 1000 -2000 μg kg -1 bw [23], with a described LD 50 of 880 μg kg -1 bw [24,25]. Some studies have reported values of DTX1 lethal dose below 300 μg kg -1 bw while others reported no deaths in mice at the oral dose 750 μg kg -1 bw [19,[26][27][28]. Regarding DTX2 an oral LD 50 of 2262 μg kg -1 bw has been recently established [29].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations